Efficacy of Stereotactic Body Radiotherapy for Recurrent or Residual Hepatocellular Carcinoma after Transcatheter Arterial Chemoembolization - Wu, Fasheng; Lin, Lianxing; Liu, Jianmin; Huang, Hecheng; Han, Fei; Wu, Xianheng; Zheng, Yinyan; Zhao, Xiaofang; Chen, Jinghong; Yao, Erhua; Liang, Ping (BioMed research international, 2018)
Aim. To evaluate the efficacy and toxicity of hypofractionated stereotactic body radiotherapy (SBRT) for patients with recurrent or residual hepatocellular carcinoma (HCC) after transcatheter arterial chemoembolization (TACE). Methods. Between June 2008 and July 2015, thirty-three patients with HCC were treated by SBRT. There were 63 lesions in 33 patients. A total dose of 39–45 Gy/3–5 fractions was delivered to the 70–80% isodose line. Results. Objective response rate (CR + PR) was 84.8% at 6 months. The overall survival rate was 87.9%, 75.8%, 57.6%, and 45.5% at 6, 12, 18, and 24 months, respectively. Median overall survival was 19 months. At 3 months, AFP decreased by more than 75% in 51.5% of patients (17/33). Overall survival was significantly different ( P < 0.00 1 ) between the group of patients for whom AFP decreased more than 75% and the group for whom AFP decreased by less than 75%. The AFP-negative rate was 48.5% (16/33) after 6 months. Eight patients (24.2%) had grade 1-2 transient fatigue, and 11 patients (33.3%) had grade 1-2 gastrointestinal reactions within 1 month. Conclusion. SBRT is a promising noninvasive and palliative treatment with acceptable toxicity for recurrent or residual HCC after TACE.